Exploring the contextual factors behind various phases in logistics sprawl: The case of Seoul Metropolitan Area, South Korea. (December 2022) - Kang, Sanggyun
Abstract: Logistics sprawl is a phenomenon that allows retailers and distributors to cope with the increasing demand for processing large freight volumes through the globalized production and distribution systems. It involves a tradeoff between per-unit inventory and transport costs. Large-scale, automated facilities are built on the urban periphery, where relatively cheaper land is more available. A potential increase in shipment distance necessitates better freight transport management and planning by logistics businesses and the public sector. At present, online shopping sales are skyrocketing, and consumers increasingly demand instant delivery at no cost. Online retailers strive to fulfill the demand in urban settings, characterized by high land rent, congestion, and strict regulations. Building an urban logistics system can become extremely costly and time-consuming. Public interventions may be justified if urban logistics is considered an essential utility that can lead to significant negative externalities without proper management. This research navigates how and where warehouse development has occurred under such stringent circumstances. I first examine the spatial dynamics of warehouse development over the last three decades in the Seoul Metropolitan Area, South Korea, and attempt to expand the conventional understanding of logistics sprawl. Relative distribution is calculated between warehouses and potential destinations: B2C consumer (population), B2B I (employment), B2B II (industrial park), and Seoul's central business district. The primary data source is the Korea National Building Registry, which contains 3340 warehouse development records. Four phases in the spatial dynamics of warehouse development are documented: stagnation (1991–1998), sprawl (1998–2007), peak (2007–2008), and return (2009–present). Further, semi-structured interviews with field experts identify the business, economic, and regulatory circumstances that potentially influence logistics facility development. The results suggest four factors behind logistics sprawl: (1) logistics restructuring driven by a consumption-based economy, (2) location factor tradeoffs, (3) disruptive economic shocks, and (4) regulatory reform. This research calls for comprehensive land use and transport planning to better accommodate urban logistics practices. Highlights: Warehouse development in 1991–2020 examined in South Korea's Seoul metro area. Relative centrality tested between warehouses and B2C/B2B consumers. Four phases in warehouse development are stagnation, sprawl, peak, and return. Factors: consumer economy, factor tradeoff, external shock, and regulatory reform Comprehensive land use/transport planning crucial for efficient urban logistics.